Sex-based analysis of clinical outcomes in elderly patients with esophageal squamous cell carcinoma post-esophagectomy: a propensity score matching analysis - Kexun Li; Kexun Li; Simiao Lu; Simiao Lu; Changding Li; Changding Li; Jie Mao; Huan Zhang; Kangning Wang; Guangyuan Liu; Yunchao Huang; Yongtao Han; et al. (Frontiers in Oncology)
BackgroundEsophageal squamous cell carcinoma (ESCC) is a common and aggressive form of esophageal cancer, particularly prevalent in East Asia. This study aimed to investigate the impact of sex on clinical outcomes, including survival and postoperative complications, in elderly ESCC patients following esophagectomy.MethodsWe conducted a retrospective cohort study using data from the Sichuan Cancer Hospital & Institute Esophageal Cancer Case Management Database, involving patients aged 70 years and older who underwent esophagectomy from May 2016 and August 2021. Patients were grouped by sex, and subgroup analyses were performed on non-smoking, non-drinking patients. OS and DFS were analyzed using the Kaplan-Meier method, and between-group comparisons were conducted using the log-rank test. Propensity score matching (PSM) was applied to adjust for potential confounders.ResultsAlthough females showed a longer median OS (60.2 months) compared to males (40.0 months), the difference was not statistically significant after PSM (HR = 0.885, P = 0.573). Similarly, no significant differences were observed in DFS between sexes. In non-smoking, non-drinking subgroups, OS and DFS remained higher but without significant sex-based differences. Postoperative adverse events such as pulmonary infection and anastomotic leakage were common across groups.ConclusionsWhile sex does not significantly affect OS and DFS in elderly ESCC patients, male patients may experience higher rates of certain postoperative complications, such as abnormal liver function and pneumothorax.